SURGICAL TACTICS IN DISTAL LESIONS OF NERVE TRUNKS OF THE UPPER LIMBS - M.F. ODINAEV; G.M. KHODZHAMURADOV; A.KH. SHAYMONOV; M.S. SAIDOV (Паёми Сино, 2019)
Objective: Optimization of the results of microsurgical reconstruction of the nerve trunks of the upper limb with their complete anatomical break at the distal level